Income Distribution in Colombia - Berry, R. Albert; Urrutia, Miguel (New Haven : Yale University Press, 1976)
This text focused on design to test significant general hypothesis concerning the problem of economic growth and which draw on quantitative information from national economic accounts and other sources.
Includes bibliographical references and index.
Loans
osa;03/08/17
Keywords: Income distribution